2015
DOI: 10.1186/s12889-015-2619-z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy burden of intestinal parasite infections in Kalena Rongo village, a rural area in South West Sumba, eastern part of Indonesia: a cross sectional study

Abstract: BackgroundIntestinal parasitic infections (IPIs) are one of the major public health problems, especially in the rural area of developing countries with low socio-economic status and poor sanitation. The study was aimed to determine the prevalence of IPIs among the inhabitants of a rural area in South West Sumba, eastern part of Indonesia.MethodsA cross-sectional study was done in Kalena Rongo village, South West Sumba in April 2014. Stool samples were collected and examined for IPIs using direct smear method.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
7
25
1
3
Order By: Relevance
“…Generally, this can be explained by the poor sanitary and hygiene conditions, effects of contaminated water supplies, exposure to soil, and absence of toilet facilities. 1,43 On the contrary, Kiani and others found no statistical difference in blastocystosis rates between rural and urban residents, 26 which support our results. In our study population, 36% of the individuals frequently traveled to Turkey and European countries.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Generally, this can be explained by the poor sanitary and hygiene conditions, effects of contaminated water supplies, exposure to soil, and absence of toilet facilities. 1,43 On the contrary, Kiani and others found no statistical difference in blastocystosis rates between rural and urban residents, 26 which support our results. In our study population, 36% of the individuals frequently traveled to Turkey and European countries.…”
Section: Discussionsupporting
confidence: 77%
“…Numbers of female and male participants were 143 (62.2%) and 87 (37.8%), respectively. Distribution of the individuals according to the age groups was nine (3.9%) for age 7-19, 76 (33%) for age 20-39, 90 (39.1%) for age [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59], and 55 (24%) for age 60 and above. A minority of the participants (24%) were university graduates; however, most of the individuals (91.7%) had middle or high socioeconomic status.…”
Section: Resultsmentioning
confidence: 99%
“…This is understandable, given that the study location is one of the most prevalent areas of soiltransmitted helminth (STH) infections. [3] It was found that girls had a higher proportion of STH infection compared with boys in all types of infection. This finding accords with a study in Kenyan school-aged children, in which females had a higher proportion of infection than males.…”
Section: Discussionmentioning
confidence: 96%
“…This disease is a community health problem, especially in areas where poverty is prevalent, along with a low socioeconomic status and unhealthy hygiene habits [1,2]. In the Sumba Barat Daya District, Indonesia, the prevalence of trichuriasis is as high as 64%, and the disease is of great concern throughout Indonesia [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Use of potable water is thus limited to drinking and cooking, and unclean water is used for bathing and for washing the hands and face. 15 Conjunctivitis occurred most often among infectious cases (52.7%) with the highest proportion being among young adults. 16 In reality, many toddlers also suffer from conjunctivitis but parents rarely seek medical care as it is considered normal and self-healing without medications.…”
Section: The Analysis Of Medical Records Frommentioning
confidence: 99%